EVALUASI KELAYAKAN KINERJA PEMUTUS TENAGA (PMT) 70 kV PADA BAY ARJAWINANGUN 1 DI GARDU INDUK SUNYARAGI - Yuka, Helmi Dwi; Utomo, Teguh; Dhofir, Moch. (Jurnal Mahasiswa TEUB, 2024)
Power Breakers (PMT) are one of the important equipment in the electricity system at the main substation. Damage to the PMT is very dangerous and disrupts the operation of the system, so periodic testing must be carried out to ensure that the PMT is suitable for operation. Tests on PMT are insulation resistance testing, contact resistance testing, grounding resistance testing, contact simultaneity testing, and SF6 gas testing. This research aims to evaluate whether the PMT in the Arjawinangun 1 bay at the Sunyaragi Main Substation is still effective and safe to operate, namely by using analysis of a set of data taken based on the values produced by routine testing or maintenance. This research was carried out by comparing the test results obtained with the standard values for each test. The insulation resistance test results obtained for each phase have values above 70 MΩ. The results of contact resistance testing carried out on each phase have values below 50 µΩ. The results of the grounding resistance test on each phase have a value below 1Ω. In the simultaneity test, the delta time calculation results obtained for both open and close times were each below 10 ms. The results of SF6 gas purity testing have a purity value above 99%. Based on the results of testing for insulation resistance, contact resistance, grounding resistance, contact simultaneity and SF6 gas purity, the PMT installed in Arjawinangun 1 bay is still in a safe condition and suitable for operation because it complies with standards. Keywords—Power Breaker (PMT), Insulation Resistance, Contact Resistance, Grounding Resistance, Contact Simultaneity, SF6 Gas Purity